PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SDN 011 SIDOREJO KECAMATAN SIMPANG KANAN - ', Erliandi; ', Lazim N; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research was aimed to increase learning process and student achievement of social lesson in V grade year of 2015/2016. The subject of this research is student V grade of State Elementary School 011 Sidorejo Wich is total of 18 student, consisted of 10 girls and 8 boys. This was a classroom research wich has to cycles wich was conducted on April 6th to 25 nd 2016. The data shown that either learning process or student’ achievement increase. First cycle at the firs meeting teacher activity was 62,50% categorized as enough and increased 8,33% at the second meeting as 70,83%. Categorized is enough. Meanwhile at the second cycle at the first meeting the percentage of teacher activity increased as 83,33% categorized as good and in the scond meeting it increased as 12,5% so the percentage become 95,83% categorized as very good. Whil student activities in learning process also increased. At the first cycle in the first meeting, the percentage of student activities was 58,33% categorized as minus and the scond meeting it increased as 8,33% so became 66,66% categorized as enougt. At the scond cycle in the first meeting it increased to 83,33% categorized as good. At the scond meeting the percentage of student activities as 12,5% became 95,83% categorized as very good. Student learning outcomes also increased grom baseline to daily test of I that the average 63,27 be 70,55. The percentage increase in the initial score to the daily test I of 10,31%, of daily test I to daily test II of 14,67%. Mastery learning student of the initial score as many 6 peoples the completion of the 18 student with a percentage of 23,33%. In the fist cycle increased to 8 people punished with percentage 44,44%. The second cycles increased to 15 peoples complete with a percentage of 83,33%. Of these discussions can be conclude with the implementation of inquiry learning can be improve learning outcomes of social science in grade five of SDN 011 Sidorejo Simpang Kanan districts.Key Words : Inquiry learning model, science of primary school, out comes.